you confused me too
I will start again with
LS = 1 + cot^2 y
= 1 + cos^2 y/sin^2 y , now find a common denominator
= (sin^2 y + cos^2 y) / sin^2 y, but sin^2 y + cos^2 y=1
= 1/sin^2 y
= RS
Let y represent theta
Prove:
1 + 1/tan^2y = 1/sin^2y
My Answer:
LS:
= 1 + 1/tan^2y
= (sin^2y + cos^2y) + 1 /(sin^2y/cos^2y)
= (sin^2y + cos^2y) + 1 x (cos^2y/sin^2y)
= (sin^2y + cos^2y) + (sin^2y + cos^2y) (cos^2y/sin^2y)
= (sin^2y + cos^2y) + (sin^2y + cos^2y)(sin^2y) / (sin^2y)(cos^2y/sin^2y)
... And now I confuse myself
Where did I go wrong? And please direct me on how to fix it?
7 answers
I'm not suppose to use the inverse identities yet ...
ok, then in
LS = 1 + 1/tan^2y
= 1 + 1/(sin^2 / cos^2 y)
= 1 + (cos^2 y)/(sin^2 y)
= ... my second line
surely you are going to use tanx = sinx/cosx !!!
we are not using "inverse identities" here
LS = 1 + 1/tan^2y
= 1 + 1/(sin^2 / cos^2 y)
= 1 + (cos^2 y)/(sin^2 y)
= ... my second line
surely you are going to use tanx = sinx/cosx !!!
we are not using "inverse identities" here
I meant the reciprocals of SOH CAH TOA
And ... I just got it
Here's my answer:
LS:
= 1 + 1/tan^2y
= 1 + 1/(sin^2y/cos^2y)
= 1 + 1(cos^2y/sin^2y)
= 1 + cos^2y / sin^2y
= 1 + 1-sin^2y / sin^2y
= 1(sin^2y) / sin^2y + 1 - sin^2y / sin^2y
= sin^2y + 1 - sin^2y / sin^2y
= 1/sin^2y
And ... I just got it
Here's my answer:
LS:
= 1 + 1/tan^2y
= 1 + 1/(sin^2y/cos^2y)
= 1 + 1(cos^2y/sin^2y)
= 1 + cos^2y / sin^2y
= 1 + 1-sin^2y / sin^2y
= 1(sin^2y) / sin^2y + 1 - sin^2y / sin^2y
= sin^2y + 1 - sin^2y / sin^2y
= 1/sin^2y
yes
correct
correct
should have taken a closer look at your solution.
the last few lines make no sense with "no brackets" being used
why don't you follow the steps of my original solution, it is so straightforward.
the last few lines make no sense with "no brackets" being used
why don't you follow the steps of my original solution, it is so straightforward.
cscx-cotx forms an identity with?